2004
DOI: 10.1021/bi049910+
|View full text |Cite
|
Sign up to set email alerts
|

Decavanadate Binding to a High Affinity Site near the Myosin Catalytic Centre Inhibits F-Actin-Stimulated Myosin ATPase Activity

Abstract: Decameric vanadate (V 10 ) inhibits the actin-stimulated myosin ATPase activity, noncompetitively with actin or with ATP upon interaction with a high-affinity binding site (K i ) 0.27 ( 0.05 µM) in myosin subfragment-1 (S1). The binding of V 10 to S1 can be monitored from titration with V 10 of the fluorescence of S1 labeled at ethylenediamine (IAEDANS) or 5-(iodoacetamido) fluorescein, which showed the presence of only one V 10 binding site per monomer with a dissociation constant of 0.16-0.7 µM, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 56 publications
11
78
0
Order By: Relevance
“…Vanadium toxicity studies often disregard the formation of different vanadate oligomers known to have different biochemical effects and to interact with high affinity with many proteins such as, for example, myosin [5]. Few animal studies involving vanadium consider the contribution of different oligomeric vanadate species to vanadium toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vanadium toxicity studies often disregard the formation of different vanadate oligomers known to have different biochemical effects and to interact with high affinity with many proteins such as, for example, myosin [5]. Few animal studies involving vanadium consider the contribution of different oligomeric vanadate species to vanadium toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…As decavanadate is eventually less permeant through the anionic channel than the other vanadate oligomers and likely to be bound with high affinity to proteins, therefore preventing its disintegration to vanadate oligomers and reduction to vanadyl, we suggest that the accumulation of vanadium in liver after decavanadate administration is a consequence of a higher level of exposure of liver to total vanadium. It is known that decavanadate binds with high affinity with proteins [4,5,8]. Moreover, it was demonstrated that, in certain experimental conditions (but at physiological pH), the half-life of 100 lM decameric vanadate species, as ascertained by UV/vis, increases from 5 to 15 h, in the presence of the calcium pump from sarcoplasmic reticulum (Aureliano and Gândara, in press).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation of myosin S1 Mg 2+ -ATPase activity by F-actin was measured spectrophotometrically at 340 nm using the coupled enzyme pyruvate kinase/lactate dehydrogenase (0.42 mM phosphoenolpyruvate, 0.375 mM NADH, 18 U of lactate dehydrogenase, and 18 U of pyruvate kinase), as in Tiago et al 9 …”
Section: Measurements Of F-actin Stimulated S1-mg 2+ -Atpase Activitymentioning
confidence: 99%
“…Thereafter, vanadium has a variety of physiological effects acting either as a phosphate analogue in the monomeric form ðH 2 VO À 4 Þ or through oligomeric vanadate species. Thus, vanadium showed to be a powerful biochemical tool to gain a deeper knowledge in several biochemical mechanisms such as the regulation of muscle contraction and the modulation of the F-actin stimulated myosin ATPase activity and its relevance to actin-myosin interactions [6,7].…”
Section: Introductionmentioning
confidence: 99%